Environmental Health Research 2000–2026 Topic Landscapes Collaboration Patterns and Influential Sources: A Bibliometric Mapping - Judijanto, Loso (Westscience Press, 2026)
This study aims to map the intellectual landscape, thematic evolution, collaboration patterns, and influential sources in environmental health research from 2000 to 2026 using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, co-authorship networks, and citation structures. The results indicate a significant growth in environmental health research, reflecting increasing global concern over environmental risks and their impact on human health. The co-occurrence analysis reveals three dominant thematic clusters: epidemiological studies focusing on environmental exposure and disease outcomes, toxicological and biological research exploring mechanisms of exposure, and environmental risk assessment emphasizing pollution, sustainability, and mitigation strategies. Density visualization highlights core research areas such as epidemiology, risk assessment, health risks, and public health, while also identifying emerging topics including climate change, microplastics, and sustainable development. Furthermore, the study finds that international collaboration has expanded, with increasing contributions from developing regions, although disparities in research distribution remain evident. Influential sources are primarily concentrated in high-impact journals within environmental science and public health domains. This study provides a comprehensive understanding of the structure and development of environmental health research and offers insights for future research directions, particularly in integrating emerging environmental challenges and strengthening global collaboration.